Decorative Motifs on the Woven Cloth: Local and Indonesian Fine Arts Education Study - Jayadi, Jayadi; Ahmad, Abd. Aziz; Yunus, Pangeran Paita (ETDC: Indonesian Journal of Research and Educational Review, 2025)
This study aims to analyze the meaning of motifs, functions of motifs, and functions of bebet woven fabrics in the Sasak Ende community in terms of education and economy. This study uses a qualitative approach with an ethnographic approach, in-depth interviews, and documentation. We conducted this study in the Sasak Ende Tourism Village, Central Lombok Regency. Data analysis was carried out in the stages of data reduction, data presentation, and drawing conclusions. The results of the study showed that the kembang komak putiq woven cloth (white komak bean motif) is one of the oldest woven cloths with geometric patterns in the form of vertical lines and horizontal lines, forming a checkered motif that has been woven from generation to generation, Selentang (animal feet, Ragi bararti bumbu Bingkal means "animal feet" (buffalo) and Orong means "road." Maten kao (buffalo eyes) Biwih kaing (mouth of the cloth). The kembang komak putiq woven cloth (white komak flower) contains symbolic meaning and symbolic function in traditional events related to traditional rituals, traditions, and Sasak culture. The symbolic meaning of the motif includes religious values, aesthetic values, and education. This motif presents the identity of Sasak culture, spirituality, and the relationship between humans and the surrounding environment. Currently, the Sasak Ende community uses the kembang komak white woven cloth as an educational and economic value. The community faces challenges in sustainably inheriting weaving skills because of the rapid influence of technology, lifestyle changes, education, and contemporary demands on the current generation.